2018
DOI: 10.1186/s13071-018-3136-6
|View full text |Cite|
|
Sign up to set email alerts
|

Urogenital schistosomiasis elimination in Zanzibar: accuracy of urine filtration and haematuria reagent strips for diagnosing light intensity Schistosoma haematobium infections

Abstract: BackgroundUrine filtration and microhaematuria reagent strips are basic standard diagnostic methods to detect urogenital schistosomiasis. We assessed their accuracy for the diagnosis of light intensity infections with Schistosoma haematobium as they occur in individuals living in Zanzibar, an area targeted for interruption of transmission.MethodsUrine samples were collected from children and adults in surveys conducted annually in Zanzibar from 2013 through 2016 and examined with the urine filtration method to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
76
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(87 citation statements)
references
References 30 publications
(38 reference statements)
8
76
3
Order By: Relevance
“…However, four samples had counts between six and 721 eggs and it is not clear, why no DNA amplification occurred. There was no indication that storage time since sample collection, location of the participant's residence, sex or the microhaematuria level influenced the qPCR outcome in our study here, but labelling errors in 3% of samples have been suggested as potential reason for discrepant diagnostic results in another study from Zanzibar working with urine samples from the same surveys [7]. Most of the microhaematuria-positive but egg-negative and Dra1 DNA-negative urine samples were from females, and the explanation that the microhaematuria was caused by menstruation blood or other infections of the urogenital tract is self-evident.…”
Section: Discussioncontrasting
confidence: 61%
See 2 more Smart Citations
“…However, four samples had counts between six and 721 eggs and it is not clear, why no DNA amplification occurred. There was no indication that storage time since sample collection, location of the participant's residence, sex or the microhaematuria level influenced the qPCR outcome in our study here, but labelling errors in 3% of samples have been suggested as potential reason for discrepant diagnostic results in another study from Zanzibar working with urine samples from the same surveys [7]. Most of the microhaematuria-positive but egg-negative and Dra1 DNA-negative urine samples were from females, and the explanation that the microhaematuria was caused by menstruation blood or other infections of the urogenital tract is self-evident.…”
Section: Discussioncontrasting
confidence: 61%
“…Subsequently, urine samples with sufficient volume were vigorously shaken, and 10 ml were filtered through a filterholder containing a polycarbonate filter with a pore size of 20 μm (Sterlitech, Kent, WA, United States of America) using a standard 10 ml plastic syringe. The filter was then carefully transferred to a microscope slide, which was labeled with the participant ID, covered with hydrophilic cellophane soaked in glycerol, stained with Lugol's iodine and examined under the microscope for the presence and number of S. haematobium eggs by trained laboratory technicians [7]. Finally, on the day of collection, 10 ml of 10% of all urine samples were filled into Falcon tubes and stored in a − 20°C freezer in Pemba for future use.…”
Section: Laboratory Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…In highly endemic areas, detection of hematuria could serve as a proxy indicator for S. haematobium infection identification (Anosike et al 2001;French et al 2007;Houmsou et al 2011). The validity of haematuria as a diagnostic criterion for urinary schistosomosis screening was discussed in a number of publications (Kinget al, 2013;Krauth et al 2015;Ochodoet al, 2015;Knopp et al, 2018). In our study, dipstick test sensitivity and specificity for detection of egg-positive urine were estimated at 68 % and 74 %, respectively (Table 3).…”
Section: Date Of Collectionmentioning
confidence: 99%
“…Some of these challenges include accurately estimating clinical morbidity, evaluating the impact of programmatic interventions, diagnosing preschool aged children and assessing new diagnostic tools (Stete et al, 2012;Knopp et al, 2013Knopp et al, , 2018Le and Hsieh, 2017). Recent concern has also been raised about urine-egg microscopy's poor sensitivity when attempting to detect 'ultra-light' infections, regarded as those that result in the expulsion of between only one and five eggs per 10 mL of urine (Knopp et al, 2018). Given the reproductive biology of schistosomes, just one infected individual excreting such minute numbers of eggs that may go on to infect and asexually reproduce within the appropriate intermediate freshwater snail host, potentially producing hundreds of cercariae per day, can cause the re-infection of an entire community (Colley et al, 2014).…”
Section: Microscopic Changes To Urine As a Means Of Diagnosing Urogenmentioning
confidence: 99%